A statistical detection mechanism for node misbehaviours in wireless mesh networks. (14th May 2019) - Khatoun, Rida; Begriche, Youcef; Khoukhi, Lyes
Wireless mesh networks (WMNs) have become an increasingly popular wireless networking technology for establishing the last-mile connectivity for home and neighbourhood networkings. In such networks, packet dropping may be due to either an attack, or normal loss events such as bad channel quality. Furthermore, in the route discovery phase, path stability is not always considered. We consider a special case of denial of service (DoS) attack in WMNs known as the greyhole attack. In this attack, a node selectively drops some packets which it has to forward along the path. To mitigate this attack, we propose a dropping detection mechanism allowing a mobile node to select a most reliable route to the destination. Our detection module detects misbehaving nodes by comparing the observed packet loss distribution of nodes to the expected ones when they are well-behaved. We validate the proposed approach via extensive simulations through R software and Matlab.